Case Report: Postacute Rehabilitation of Guillain-Barré Syndrome and Cerebral Vasculitis-Like Pattern Accompanied by SARS-CoV-2 Infection - Colonna, Stefano; Sciumé, Luciana; Giarda, Federico; Innocenti, Alessandro; Beretta, Giovanna; Dalla Costa, Davide (Frontiers in Neurology, 2021)
Abstract Introduction The main clinical manifestation of the novel Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is the respiratory involvement. Neurological manifestations are being recognized increasingly, including febrile seizures, headache, dizziness, myalgia, as well as encephalopathy, encephalitis, stroke and acute peripheral nerve diseases. Cerebral vasculitis is rarely reported. We describe a case of SARS-CoV-2 interstitial pneumonia complicated by flaccid tetraplegia due to Guillain-Barré Syndrome (GBS) associated with cerebral vasculitis-like pattern. Case description A 62-year-old man was hospitalized for cough, fever and severe respiratory failure requiring tracheal intubation and invasive ventilation. The chest Computerized Tomography (CT) showed images related to interstitial pneumonia and the subsequent nasopharyngeal swab confirmed the detection of SARS-CoV-2 infection. During the hospitalization, there was a progressive deterioration of the sensory associated with areflexic flaccid tetraplegia. The treatment with high-dose of immunoglobulin G (IgG) led to the immediate improvement of the general conditions and partial response in terms of recovery of the upper limb and of the distal lower limb movements. Subsequently, the patient was admitted to our Rehabilitation Unit, where he received intensive rehabilitation treatment consisting of physiotherapy and occupational therapy. Two months later the patient was discharged at home, able to walk independently even for long distances thanks to the use of Ankle-Foot Orthosis (AFO). Conclusion In this report, we present the case of a patient with peripheral and central neurological damage that occurred later severe pneumonia induced by SARS-CoV-2. The Immunoglobulin G therapy allowed the patient to benefit considerably from early rehabilitation, reaching the walking, increasing the independence in daily living tasks, and enabling safe discharge from hospital to home. Related neurologic complications of SARS-CoV-2 infection suffer a lack of understanding and further investigations should be conducted.